Effects and Health - Related quality of life changes among patients undergoing uterine fibroids embolisation in Hue Central Hospital - Tu, Hoang Ngoc; Phuong, Phan Le Vy; Ngoc, Hoang Thi Bich; An, Le Si Phuc; Cat, Le Duy (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Uterine fibroids (UF) are the most common neoplasms of the female pelvis. The current treatment trend is to use noninvasive methods such as uterine fibroids embolization to reduce severe symptoms and improve the quality of life. The study’s main objective was to investigate the clinical features and treatment results after 2 years of uterine fibroids embolisation to evaluate the effectiveness and improve the symptoms of uterine fibroids. The secondary objective is to evaluate changes in the quality of life and potential relationships with age, number of children, volume and number of fibroids compared to before embolism. Methods: All patients with uterine fibroids had been treated with uterine fibroid embolisation therapy at Hue Central Hospital between 2012 and 2018. Study period: 02 years, since the patient received treatment. Method of the study was retrospective cross-sectional description at the time before and 2 years after treatment. Use the uterine fibroid symptom and quality of life questionnaire to collect data. Results: There were twenty patients treated by Uterine fibroid embolisation. About age: 85% in the age group 30 - 50 years old; The number of patients with infertility caused by fibroids accounts for 30%; 65% of patients were in rural areas. Clinical characteristics: 50% of patients with mild anemia before treatment; 55% had 2-5 fibroids; The largest fibroids in the muscle account for 30%. Regarding treatment after 2 years, the reduction in symptoms of uterine fibroids after treatment was statistically significant, with an overall reduction of 16% (95% CI 12 to 20, P <0.01). The improvement in the health-related quality of life (HRQOL) score was 21.7% (95% CI 13.4 to 30, P <0.01). There are 3 cases, accounting for 15%, needing surgical intervention after treatment. Conclusions: Treatment of uterine fibroid embolisation (UFE) has been shown to improve symptoms after 2 years, helping patients keep uterus and improving the quality of life. Uterine fibroid embolisation may be an option for patients with large, subserous, or sub-endometrial fibroids. Cases in the uterine muscle will be less effective